1999
DOI: 10.1016/s0893-133x(99)00070-6
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2 Adrenergic Modulation of Prefrontal Cortical Neuronal Activity Related to Spatial Working Memory in Monkeys

Abstract: The prefrontal cortex (PFC) plays a critical role in regulating spatial working memory (SWM) (Fuster et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
105
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 32 publications
5
105
2
2
Order By: Relevance
“…Given the beneficial effects of clonidine and related a 2 agonists on prefrontal cortical function (Li et al, 1999;Wang et al, 2007) as well as the important role of the prefrontal cortex in the positive actions of a 2 agonists on spatial working memory (Arnsten and Goldman-Rakic, 1985;see Arnsten, 2004 for review), it is likely that if clonidine improves memory in either model, this phenomenon would be linked to enhanced prefrontal cortical function. In the case of animals with hippocampal damage, the enhancement of prefrontal function could act to compensate for the loss of hippocampal modulation of spatial working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Given the beneficial effects of clonidine and related a 2 agonists on prefrontal cortical function (Li et al, 1999;Wang et al, 2007) as well as the important role of the prefrontal cortex in the positive actions of a 2 agonists on spatial working memory (Arnsten and Goldman-Rakic, 1985;see Arnsten, 2004 for review), it is likely that if clonidine improves memory in either model, this phenomenon would be linked to enhanced prefrontal cortical function. In the case of animals with hippocampal damage, the enhancement of prefrontal function could act to compensate for the loss of hippocampal modulation of spatial working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Our work showed that both systemic administration and local infusion of guanfacine into the PFC improve visuomotor associative learning [70,75] . Using an iontophoretic technique, stimulation of α 2A -adrenoceptors in the PFC was found to increase the spiking activity associated with working memory in behaving monkeys [37,76] .…”
Section: Prefrontal α 2a -Adrenoceptor Stimulation Ameliorates Cognitmentioning
confidence: 99%
“…In this paper, we review research progress in the relevant fi elds, focusing on the potential relationship between prefrontal α 2A -adrenoceptors and ADHD in nonhuman primates [35][36][37][38][39] . including poor attention regulation [40] , limited working memory [41] , and inability to inhibit inappropriate motor activity [42] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations